Analysis Of The Impact Resistance Of Adhesively Bonded, Curved Polycarbonate Windshields - Bühler, L.; Ritt, S. A.; Schlie, D.; Toso, N.; Voggenreiter, H.; Tretter, M.; Kronhofmann, P.; Leege, E. (My University, 2025)
Polycarbonate windshields have superior impact properties but deform significantly during impact. In this paper, the deformation during impact with a soft impactor was measured and compared to simulation results. A cylindrical windshield with a length of 1400 mm and a radius of 460 mm, derived from a real geometry, was impacted with an artificial bird at 65 m/s. To measure the full-field deformation in the impact area, a film with a printed speckle pattern was applied on the windshield and 3D Digital Image Correlation (DIC) was used. The finite element simulations were performed in LS-DYNA. To enable a comparison of the deformations, the subset midpoints of the DIC results were used as history nodes in the simulation. This method facilitated the identification of regions that exhibited varying degrees of deformation and enabled both qualitative and quantitative comparisons to be made.